Omega-3 Fatty Acids and Cardiovascular Disease: A Narrative Review for Pharmacists. (November 2021) - Patel, Dhiren; Busch, Robert
Background: Atherosclerotic cardiovascular disease is a significant cause of morbidity and mortality worldwide. While use of statin therapy has improved management of lipids, an unmet need in reducing residual atherosclerotic cardiovascular disease risk and ischemic events persists. We provide an overview of the pharmacology of omega-3 fatty acids, omega-3 fatty acid cardiovascular outcomes trials, landmark clinical data and pharmacology of icosapent ethyl (a stable and highly purified ethyl ester of eicosapentaenoic acid), and the critical differences between fish oil supplements and prescription omega-3 fatty acids. Method: A PubMed literature review was conducted in April 2020 to identify articles discussing omega-3 fatty acid cardiovascular outcomes trials, pharmacology of icosapent ethyl, and the evaluation of fish oil dietary supplements and prescription omega-3 fatty acids. Results: Both eicosapentaenoic acid and docosahexaenoic acid have been widely associated with positive health benefits; however, data are inconsistent regarding the benefit of combination eicosapentaenoic acid and docosahexaenoic acid in patients with cardiovascular disease. Eicosapentaenoic acid, and specifically icosapent ethyl, has demonstrated atherosclerotic cardiovascular disease risk reduction among statin-treated patients. Important clinical differences exist between dietary supplement and prescription omega-3 fatty acid products. Conclusions: As research regarding the optimal management of dyslipidemia continues, additional therapy beyond statins is necessary to reduce atherosclerotic cardiovascular disease risk. In large cardiovascular outcomes trials, eicosapentaenoic acid has demonstrated cardiovascular benefit. Icosapent ethyl possesses a favorable efficacy and safety profile and should be considered as an adjunct to statin therapy to reduce ischemic event risk.